2021
DOI: 10.3390/v13020258
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of Nucleic Acid Vaccines for One Health

Abstract: The ongoing SARS-CoV-2 pandemic has highlighted both the importance of One Health, i.e., the interactions and transmission of pathogens between animals and humans, and the potential power of gene-based vaccines, specifically nucleic acid vaccines. This review will highlight key aspects of the development of plasmid DNA Nucleic Acid (NA) vaccines, which have been licensed for several veterinary uses, and tested for a number of human diseases, and will explain how an understanding of their immunological and real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 97 publications
0
12
0
1
Order By: Relevance
“…The DNA vaccines can be designed and produced quickly once the genetic sequence is known and adapted rapidly to new emerging viral variants of concern. Clinically, the DNA vaccine modality is generally regarded as safe and is immunogenic in many different mammalian species including man 2 , 3 . Inducing both broad antibody and cellular immune responses, DNA vaccines have the potential to reduce both infection and disease.…”
Section: Introductionmentioning
confidence: 99%
“…The DNA vaccines can be designed and produced quickly once the genetic sequence is known and adapted rapidly to new emerging viral variants of concern. Clinically, the DNA vaccine modality is generally regarded as safe and is immunogenic in many different mammalian species including man 2 , 3 . Inducing both broad antibody and cellular immune responses, DNA vaccines have the potential to reduce both infection and disease.…”
Section: Introductionmentioning
confidence: 99%
“…DNA immunization has the advantage of priming the immune system in the presence of maternal antibodies. However, DNA induced immune response will mostly cell mediated (through CD8 T cell response) with weak humoral immune response (Fomsgaard and Liu, 2021). In contrast to DNA vaccine, in which the immune response closely resembles natural infection, the immune Similarly, earlier studies also showed active stimulation of CMI following rgD and gD plasmid DNA immunization (Ruitenberg et al, 2000;Zhang et al, 2000).…”
Section: Rgb Immunization Restricts Virus Replication and Shedding In Immunized Micementioning
confidence: 99%
“…With regards to the search on DNA vaccines, most of the articles retrieved were on vaccines that were experimentally developed. Although many DNA vaccine candidates have been evaluated with promising results in various animal species, it has been estimated, by a recent review, that only five DNA vaccines have been approved and licensed for veterinary use [130]. These include:…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Conversely, no DNA vaccines have been licensed for human use to date [33,130]. DNA vaccination involves immunization with a plasmid encoding a gene of the pathogen.…”
mentioning
confidence: 99%